Internet Security Awareness of Filipinos - Omorog, Challiz D.; Medina, Ruji P. (International Journal of Computing Sciences Research, 2018)
Purpose – This paper examines the Internet security perception of Filipinos to establish a need and sense of urgency on the part of the government to create a culture of cyber security for every Filipino. Method – A quantitative survey was conducted through traditional, online and phone interviews among 252 respondents using a two-page questionnaire that covers basic demographic information and two key elements ? (1) Internet usage and (2) security practices. Results – Based on findings, there is a sharp increase of Internet users for the last three years (50%) and most access the Internet through mobile (94.4%). Although at home is the most frequent location for Internet access (94.4%), a good percentage still use free WiFi access points available in malls (22.2%), restaurants (11.1%), and other public areas (38.9%) doing Internet services (email and downloading) that are vulnerable to cyber attacks. The study also revealed that although respondents may have good knowledge of Internet security software, proper implementation is very limited. Conclusion – Filipinos are susceptible to cyber attacks, particularly to phishing and malware attacks. Also, majority of the respondents’ Internet security perception is derivative- they practice online measure but with limited understanding of the purpose. Therefore proper education, through training and awareness, is an effective approach to remedy the situation. Recommendations – The Philippine government must now take actions and tap industries to educate Filipinos about Internet security before any negative consequences happen in the future. Research Implications – The information collected sets a clear picture on the importance of cyber security awareness from a regional to a global perspective.